Melodías de Ketty Moreno. Creación y difusión de arreglos para coro mixto - Gaona Hidalgo, Yaela Cristel (2025)
The present artistic proposal addresses the creation of choral arrangements for mixed voices of musical pieces by the singer-songwriter Ketty Moreno, with the aim of promoting her repertoire and highlighting women's role within the musical practice of Loja. The main objective is to develop five arrangements for mixed choir of Ketty Moreno's Latin American genre pieces. The methodology was divided into three phases. The first phase involved the recognition and selection of pieces to transcribe using a registration and observation form. In the second phase, choral arrangements were developed following a documentary analysis of bibliographic sources related to the different choral techniques and resources that could be employed in the arrangements. In the third and final phase, the arrangements were presented through a recital at the Theatre Simón Bolívar in Loja, where three of them were performed. The result of this work is the creation of five choral arrangements: Te voy a dejar vivir, De que te sirve, Maria Antonia, Nuestro Tango and Estaba escrito. These pieces feature different musical textures (monody, homophony, counterpoint), various voice movements, and choral techniques, notably vocal percussion. Finally, it was concluded that the creation of choral arrangements is an effective way to disseminate the musical repertoire of artists who have not been sufficiently recognized, while also contributing to the expansion of the choral repertoire